Mestizos, mulatos y zambos en la ciudad de Cartago (siglo XVIII) - Acuña León, María de los Ángeles (2018)
The city of Cartago was the most important administrative and political center of the colony in our country, has deserved many studies of not few social researchers, about its origin, population, demography and other subjects, so with this article, we intend to give another point of view as a reference that contributes to the knowledge of our own history. In this work we enter into the daily life of mestizos, mulattos, zambos and other mixed inhabitants of the city of Cartago. First, we refer to the origins and founding of the city; secondly, we determined the demographic evolution and spatial distribution of the mixed residents in the city and its neighborhoods; third, we review the function in the economy Colonial and urban dynamics of the mixed and, lastly, we analyze the meaning of miscegenation and the inhabitants of mixed origins in Cartago's colonial society. The investigation is based on primary sources that include documents from The National Historic Archive of Costa Rica.